The Emerging Role of Integrins in Diabetic Kidney Disease: A Systematic Review and Meta-Analysis of Their Diagnostic and Prognostic Utility for Early Risk Stratification - Mazaya Indah Brillian Amadea; Drajad Priyono (HM Publisher, 2025)
Background: Current biomarkers for diabetic kidney disease (DKD), notably albuminuria and eGFR, are markers of established renal damage, limiting opportunities for early intervention. Integrins, cell-matrix adhesion receptors integral to podocyte health, are emerging as potential upstream indicators of the initial injury that drives DKD. This systematic review and meta-analysis provide the first quantitative synthesis of the evidence on the diagnostic and prognostic utility of integrins in DKD. Methods: Following PRISMA guidelines, we systematically searched PubMed, Scopus, Embase, and Web of Science for studies published up to July 2025. We included studies that evaluated integrins in urine, serum, or tissue for the diagnosis of early DKD (microalbuminuria) or for predicting disease progression. Data were pooled using bivariate random-effects models for diagnosis and generic inverse variance models for prognosis. Results: Eight studies involving 2,874 patients met the inclusion criteria. For diagnosing early DKD, five studies (n=1,880) yielded a pooled sensitivity of 0.88 (95% CI: 0.82-0.92) and specificity of 0.85 (95% CI: 0.79-0.90). The area under the summary receiver operating characteristic curve was 0.91 (95% CI: 0.88-0.94), indicating excellent accuracy. A subgroup analysis of non-invasive samples (urine/serum) demonstrated similarly high performance. For prognosis, three prospective studies (n=1,224) showed that elevated baseline integrins were associated with a significantly increased risk of disease progression (pooled Hazard Ratio: 2.15, 95% CI: 1.65-2.79) over a median 5-year follow-up. Conclusion: Based on the current, albeit limited, evidence, integrins show significant promise as highly sensitive and specific biomarkers for the early detection and potent predictors for the progression of DKD. While these preliminary findings require validation in larger cohort studies, the measurement of non-invasive integrins may represent a valuable future tool for improving early DKD risk stratification.